2022
DOI: 10.1177/02654075211067254
|View full text |Cite
|
Sign up to set email alerts
|

Daily social media use, social ties, and emotional well-being in later life

Abstract: Older American adults are increasingly utilizing communication technologies, but research has seldom explored older adults’ daily social media use and its interface with other “offline” social ties. To explore a complementary and/or compensatory function of social media in later life, this study employed data from the Daily Experiences and Well-Being Study (2016–2017) to examine associations between daily social media use, daily social encounters, social network structure, and daily mood. Community-dwelling ol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 60 publications
0
13
0
Order By: Relevance
“…Studies show that individualistic countries such as Germany have different social media usage patterns than collectivist cultures (Sheldon et al , 2017). In addition, studies such as those by Rollero et al (2019) or Kim and Fingerman (2022) show that age moderates social media use. Therefore, characteristics such as age, gender and culture should not be ignored in the future, and moderation analyses could provide important insights in this regard.…”
Section: Discussionmentioning
confidence: 99%
“…Studies show that individualistic countries such as Germany have different social media usage patterns than collectivist cultures (Sheldon et al , 2017). In addition, studies such as those by Rollero et al (2019) or Kim and Fingerman (2022) show that age moderates social media use. Therefore, characteristics such as age, gender and culture should not be ignored in the future, and moderation analyses could provide important insights in this regard.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the use of technology-mediated communications such as text and social media has steadily increased among older adults (MacDonald et al, 2021; Pew Research Center, 2021), and were found to provide distinct social resources in late life (Kim & Fingerman, 2022). Currently, only 45% of older adults aged 65+ use social media, compared with 73% for those aged 50–64 years, and 81% for those aged 30–49 years (Faverio, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…The current analysis addresses how digital communication fits with traditional dimensions of intergenerational solidarity as perceived by older and younger generations, and how it might compensate for the harmful consequences of restricted face‐to‐face interactions in older parent and adult child pairs during the COVID‐19 pandemic. Even prior to the COVID‐19 outbreak, digital communication as a distinct form of interaction was found to benefit older adults' mental health and improve their ability to maintain connections with geographically distant family members (Kim & Fingerman, 2022; Zhang et al, 2021). In addition, one study found that young adults' digital communication with parents was positively associated with family satisfaction (Stein et al, 2016).…”
Section: Literature Reviewmentioning
confidence: 99%